Metode C4.5 Dan Naive Bayes Untuk Klasifikasi Kesehatan Mental Karyawan Di Tempat Kerja - Meilany Nonsi Tentua; Vicky Fidiantoro; Pradana Feri Ariyanto (Jurnal Dinamika Informatika, 2022)
Mental health is an important thing that we must always pay attention to. Because mental health is closely related to the health condition of our bodies. Many factors can affect our mental health at work. Examples are starting from salary issues, an environment that feels uncomfortable, and work colleagues. That way, your mental health can be affected. In this study, the C4.5 and Naïve Bayes Algorithm methods were used to classify the health of employees in their work environment. Data obtained from Kaggle which consists of 1259 records with 28 fields and has been converted into 15 fields. In this study, calculations were carried out using the Microsoft Excel formula to determine the C4.5 and Naive Bayes algorithms.